STRATEGIC ALLIANCES AS A COMPETITIVE ADVANTAGE IN THE GLOBALIZED LOGISTICS SCENARIO - de Oliveira, Marcos Antônio Maia; Rodrigues, Leonel Cezar; Ribeiro, Lucas Daniel Ramos (Future Studies Research Journal: Trends and Strategies, 2012)
This paper considers strategic alliances as a means of obtaining advantage in the globalized logistics scenario. Through a particular case study of partnership and strategic alliance between national companies (Rapidão Cometa, Expresso Araçatuba and Transportadora Americana) and an international one (FedEx Express), one may comprehend the impact on Rapidão Cometa, in as much as the increase in market share within the logistics market, as well as the subsequent consolidation before major national logistics operators, is concerned. Logistics - a field that holds a strategic function - supports the efficient management of the flow of materials / products, information and resources, both within the company and between the different organizations that participate in the entire value creation cycle. In Brazil, the perception of logistics as an integrating process and as a strategic tool came to light as of the 90´s, a decade mile stoned by rampant growth of international trade, by economic stabilization and by the privatization of infrastructure (Fleury, 2000). The environment in which companies currently operate is very complex and highly competitive. Therefore, they are seeking differentiation and the setting of competitive advantages over competitors. To achieve these goals, each tries to find its own path, however, amongst many a point in common might be perceived: the choice to apply logistics. (Ferraes Neto, 2001).